Effect of formate fluids on the shale stabilization of shale layers - Afshin Davarpanah; Behnam Mirshekari (Energy Reports, 2019)
Formate fluids are considered as one of the most efficient drilling fluids in petroleum industries, especially in shale to minimize the drilling inefficiencies during the operational performances. The objective of this study is to compare the profound impact of sodium and potassium formate fluids on the rheological properties such as apparent viscosity, plastic viscosity, yield point, fluid loss and shale recovery percentage of different drilling fluid samples. To do this, six samples with different compositions are conducted into the investigation in the laboratory conditions to measure each parameter statistically. According to the results of this experimental evaluation, potassium formate fluid has the lowest shale recovery percent (about 87%), which is indicated the shale preventive property of potassium. The mixture of sodium-potassium has the highest shale recovery (approximately 95%). Addition of Polyanionic Cellulose-Regular (PAC-R) and Polyanionic Cellulose-Ultralow (PAC-UL) has caused to increase the rheological properties of the formate fluids. Consequently, due to the excellent compatibility of formate fluid with reservoir rock, the minimum damaged has occurred to the formation.
Keywords: 330; Drilling inefficiencies; Formate fluids; Rheological properties; Shale recovery; Shale reservoirs